Investigation of crack detection properties of elastomer-based nanocomposites under cyclic strain loading with graphene and carbon black interaction filler - BOZTOPRAK, YALÇIN (My University, 2022)
In this study, the synergistic effect created by adding Graphene (GE) nanoplatelets and carbon black (CB) fillers to the rubber matrix was used to determine the high stretchable sensor properties. GE and CB-filled rubber nanocomposite (HcN) strain sensors have been shown to detect and trace crack initiation and crack propagation of different sizes under cyclic loading. Tests were performed with four different crack sizes (0, 2.5, 5, and 10 mm) at five different strain levels (0%, 5%, 10%, 15%, and 20%) to determine the strain sensing performance of the specimens. The electrical response of HcNs under loading was measured with the four-point probe technique and recorded with a high-performance data acquisition system. The progression of external cracks created by scalpel on HcNs was examined by measuring electrical resistance changes caused by cyclic strain loading between 0% and 20%. The electrical response of 4 phr and 8 phr filled HcNs behaved qualitatively similar to each other, while 1 phr filled HcNs showed a significantly different response in terms of quality and quantity. In 4 phr GE-filled specimens, the resistance increase was changed steadily depending on the crack length, and unstable conditions occurred at 5 and 10 mm crack lengths at 1 and 8 phr GE filler ratios. The flexible and stretchable elastomer-based conductive strain sensing sensors, developed with the synergistic interaction of well-dispersed carbon-based fillers in the matrix, can detect and record damaged conditions caused by cyclic loading in many application areas.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KOMPOZİTLER; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, COMPOSITES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Mechanics of Materials; General Materials Science; Physical Sciences; strain sensing; crack initiation and propagation; hybrid nanocomposites; graphene nanoplatelets; carbon black; natural rubber; cyclic loading; electrical resistance; ELECTRICAL-PROPERTIES; HYBRID NANOCOMPOSITES; RUBBER; COMPOSITES; NANOPLATELETS; PROPAGATION; NANOTUBES